Effect of Dietary Supplementation of Azolla Meal on Performance of Commercial Broiler Chicken - G. Mali, Avinash; P. Savaliya, Fulabhai; B. Gameti, Chintan; B. Patel, Atul; J. Bhagora, Nikesh; M. Lunagariya, Pravin (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
An experiment was carried out to investigate the effect of dietary supplementation of Azolla meal on performance of commercial broiler chicken. A total of 144 straight-run day-old chicks were randomly assigned to six treatments, each consisting of 4 replicates with 6 chicks totalling 24 chicks per treatment. Birds in treatment T1 were fed with control basal diet, and those in T2, T3, T4, T5 and T6 received control basal diet supplemented with 5, 10, 15, 20 and 25% Azolla meal, respectively. Body weight (BW6) and body weight gain (BWG0-6) of birds fed with diet containing 5% Azolla meal (T2) up to 6th week of age were significantly (p